Tinjauan Yuridis Pemidanaan Anak Oleh Hakim Pengadilan Negeri Pekanbaru - Anlapater, Rizki; R, Mukhlis; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Children as perpetrators of crime are also subject to criminal sanctions inside or outside depending on the section of the Criminal Code which laws were violated , not only adults but children under the age when they have been able to take responsibility for his actions then remain subject to criminal sanctions as well as adults , except for children in the general rules of the Criminal Code for the child minus 1/3 ( one third ) of the criminal penalty for adults , and after the special rules that Law No. 3 of 1997 on Juvenile Justice , the reduced ½ ( half ) of the criminal threat to people adult . Regarding sanctions on children in Act No. 3 of 1997 on Juvenile Justice , is determined by the difference of age children , the treatment distinction based on the growth and development of the physical , mental and social development , in this case an attempt is certainly much needed by decision makers in terms of this judge to carry out punishment against children. The purpose of this thesis , namely : First , criminalization children in positive law in Indonesia , Second , judicial consideration of the sentencing decision of the child by the District Court of Pekanbaru , Third , the weakness of the ruling consideration in sentencing judge in the District Court of Child in Pekanbaru.This type of research can be classified types as normative legal research. In this particular case the judge in rendering a verdict against the criminalization of children in positive law in Indonesia . This study is descriptive, the source data used secondary data consisting of primary legal materials, legal materials and legal materials tertiary secondary, data collection techniques in this study with the literature study methods or documentary studies, after the data is collected and analyzed for the conclusions drawn.From the research we can concluded that, first, Punishment of Children in Positive Law in Indonesia based on the applicable law, namely Law No. 3 of 1997 on the Juvenile Court to set punishment can only be imposed brat or criminal action, and form the subject of criminal and additional criminal. Second, the imposition of Criminal Justice Considerations in Case of Child Jurisdiction Court of Pekanbaru is divided into 2 ( two ), First juridical considerations, Second, non juridical considerations. Third , weakness of Considerations Against Judge In Child Punishment Decision on Jurisdiction Court of Pekanbaru, among others : First , Judge Children who handle juvenile criminal cases. Second : the decision of sentencing by the judge is more likely to judicial consideration. Third, defendant during the sentencing decision of the trial court judge Pekanbaru children not accompanied by Legal Counsel. Fourth, in consideration of the decision in terms of the Child Justice Act did not include No. 23 of 2002 on Child Protection. Keywords : Punishment - Children - Judge - District Court